Undue Benefits to Contractor Due to Non-Recovery of Rent by Medical College Kota in Rajasthan - CAG of India (CAG of India)
Non recovery of rent of INR 23.33 crore from the contractor for land provided by Medical College, Kota for execution of flyover work under Urban Improvement Trust, Kota due to lack of coordination between both the agencies.